Unveiling the hidden mechanisms behind cognitive achievement: a structural equation modeling approach to teacher learning, academic persistence, and school climate - Abukasim, Sudarto M.; Sutrisno, Hari; Rohaeti, Eli (Frontiers in Education, 2025)
Cognitive achievement in education results from the complex interaction between personal, institutional, and contextual factors. This study investigates how teacher learning characteristics such as instructional competence, personal efficacy, and pedagogical strategies along with school climate and students’ academic persistence, influence cognitive outcomes. The purpose of this study is to analyze the influence of teachers’ learning characters on cognitive achievement by considering the mediating role of school climate and students’ academic perseverance. This study uses a quantitative approach with a covariance-based structural equation modeling method (CB-SEM). The research sample consisted of 1,057 high school students in North Maluku Province, Indonesia. Data were collected using a Likert scale questionnaire and analyzed using SPSS 24, JASP 0.19, and SmartPLS 4. The results showed that professional competence, personal efficacy, and instructional models employed by teachers significantly affected cognitive achievement. In addition, the school climate and academic perseverance are mediators that strengthen the relationship between teachers’ learning character and students’ cognitive achievement. These findings confirm that a practical learning approach supported by a conducive school environment and students’ academic perseverance can contribute to the quality of education as it improves learning outcomes. This research provides insight into educators and education policymakers to develop effective learning strategies.